New Species of the Genus Eurytoma (Hymenoptera, Eurytomidae) from Ukraine and Israel - Zerova, M.D.; Seryogina, L.Ya. (Вестник зоологии, 2010)
Two new species: Eurytoma kuslitzkyi Zerova, sp. n. from Israel and Eurytoma cornuta Zerova, sp. n. from Ukraine are described. The first species belongs to the robusta species group, and differs from other species of this group by the structure of the mesosternal shelf with two projections. The second species belongs to the compessa species group and differs from all other species of this group by the sharp corn on mesopleura. Описаны Eurytoma kuslitzkyi Zerova, sp. n. из Израиля и E. cornuta Zerova, sp. n. с юга Украины. Первый вид относится к группе видов robusta, отличается от всех других видов этой группы формой мезостернального киля, несущего два выступа. Второй вид относится к группе compessa, отличается от других видов этой группы наличием высокого острого выступа на боках среднегруди.